Water marks our life - Lefebvre, Solange; Wacker, Marie-Theres (Concilium, 2012)
Water in danger Lena Partzsch -- "My God, it's our river, shouldn't we preserve it? Without the river, what else have we got? Sylvie Shaw -- Water in the Old Testament Erhard S. Gerstenberger -- Water as Sacrament : global water crisis and sacramental stewardship Mark L. Allman -- "Give me this water..." : the water of life in John's Gospel Pierre Letourneau -- African women and water Anne-Beatrice Faye -- Feminine waterscapes : water as a gendered subject Kuntala Lahiri-Dutt -- Life, water and liberation Marcelo Barros -- Reading the Bible after Fukushima Kumiko Kato -- Bridge that divides : the bridge of Mostar Željko Ivanković -- Water in action Mary E. Hunt -- Making peace with water Luis Infanti de la Mora -- Kateri Tekekwitha : the first indigenous saint of North America Bernadette Rigal-Cellar -- Women as pioneers at Vatican II Ida Raming